Tinjauan Kriminologis tentang Penyebaran Informasi Palsu (Hoax) Seputar Pemilu 2024 di Media Sosial Facebook - yusuf, wahyu; Riky Novarizal (Sisi Lain Realita, 2023)
In the current digital era, information technology and social media play a major role in disseminating information. But unfortunately, the negative impact of this technological development is the spread of fake news or hoaxes. Based on information from the Ministry of Communication and Information (Kominfo), the number of hoax news regarding the 2024 election has increased 10 times compared to last year. In the period 19 January 2022 – 26 October 2023, Kominfo discovered 101 election-related frauds on various social media. This number increased to 96 hoax news between 17 July and 26 November 2023. Based on this data, Facebook is the social media platform most used to spread fake news related to the election. This research was conducted using a qualitative approach. The results of this research are descriptive data to explain the phenomena encountered based on the researcher's observations. Based on analysis using strain theory, it is known that strain can make someone feel depressed, hopeless, and helpless. This can motivate someone to look for ways to achieve their goals, including spreading fake news. The strain conditions experienced by a person can also make a person more easily believe and be influenced by fake news. In the election context, supporters of one of the presidential candidates who feel discriminated against or are dissatisfied with the prevailing political system are more likely to be motivated to spread false news about the presidential candidate they support. Less educated voters also have a tendency to believe hoaxes.